The Prognostic Value of a Tumor Microenvironment-Based Immune Cell Infiltration Score Model in Colon Cancer - Tang, Xingkui; Liu, Minling; Luo, Xijun; Zhu, Mengyuan; Huang, Shan; Pan, Xiaofen (Frontiers in Oncology, 2021)
The current study aimed to construct a prognosis predictive model based on tumor microenvironment.CIBERSORT and ESTMATE algorithms were used to reveal the immune cell infiltration landscape of colon cancer. Patients were classified into three clusters by ConsensusClusterPlus algorithm. Immune cell infiltration (ICI) scores of each patient were determined by principal-component analysis. Patients were divided to high and low ICI score groups. Survival, gene expression and somatic mutation of the two groups were compared. We found that patients with no lymph node invasion, no metastasis, T1-2 disease and stage I-II had higher ICI scores. Calcium signaling pathway, leukocyte transendothelial migration pathway, MAPK signaling pathway, TGF β pathway, and WNT signaling pathway were enriched in high ICI score group. Immune-checkpoint and immune-activity associated genes were decreased in high ICI score patients. Patients in high ICI score group had better survival. Prognostic value of ICI score was independent of TMB. The ICI score model constructed in the current study may serve as an independent prognostic biomarker in colon cancer.